2020
DOI: 10.1590/1517-869220202603200625
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Relative Age Effect on Height, Motor Performance and Technical Elements of Olympic Volleyball Athletes

Abstract: Introduction The Relative Age Effect (RAE) refers to the chronological age difference that occurs between athletes of the same age category, which can benefit individuals born in the first two quartiles of the year. This phenomenon is commonly studied in team sports, yet the results are still inconsistent, especially in volleyball. Objective This study analyzed the distribution of the number of births per quartile of Olympic volleyball athletes and whether this would influence anthropometric/motor variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 27 publications
(38 reference statements)
0
7
1
Order By: Relevance
“…Similar results were reported by Lupo et al (2019) , who analyzed the initial phase of the career of 3,319 adult athletes from various team sports, and found that relatively older athletes were overrepresented in the early stage of the sports career, corroborating that RAE may prevail up to adults when it is very pervasive in the youth context. On the other hand, Solon Junior and Silva Neto (2020) did not find any RAE in Olympic volleyball players, speculating that complex factors such as refined tactical skills may reduce the impact of maturational aspects. Our results contradict the findings of Solon Junior and Silva Neto (2020) , since RAE was present in the analyzed elite male athletes.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…Similar results were reported by Lupo et al (2019) , who analyzed the initial phase of the career of 3,319 adult athletes from various team sports, and found that relatively older athletes were overrepresented in the early stage of the sports career, corroborating that RAE may prevail up to adults when it is very pervasive in the youth context. On the other hand, Solon Junior and Silva Neto (2020) did not find any RAE in Olympic volleyball players, speculating that complex factors such as refined tactical skills may reduce the impact of maturational aspects. Our results contradict the findings of Solon Junior and Silva Neto (2020) , since RAE was present in the analyzed elite male athletes.…”
Section: Discussionmentioning
confidence: 79%
“…On the other hand, Solon Junior and Silva Neto (2020) did not find any RAE in Olympic volleyball players, speculating that complex factors such as refined tactical skills may reduce the impact of maturational aspects. Our results contradict the findings of Solon Junior and Silva Neto (2020) , since RAE was present in the analyzed elite male athletes. These differences could be explained by characteristics of this sport context, in which the maturational aspects are determinant for the selection of talents in youth categories ( Campos et al, 2020 ), favoring relatively older athletes who usually present an anticipated maturation process (height and muscle mass) compared to younger athletes ( Malina et al, 2015 ).…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations